Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1007/s00262-002-0277-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular requirements for CD8-mediated rejection of a MUC1-expressing pancreatic carcinoma: implications for tumor vaccines

Abstract: Previous studies have indicated that different effector cells are required to eliminate MUC1-expressing tumors derived from different organ sites and that different vaccine strategies may be necessary to generate these two different MUC1-specific immune responses. In this study, we characterized molecular components that are required to produce immune responses that eliminate Panc02.MUC1 tumors in vivo by utilizing mice genetically deficient in molecules related to immunity. A parallel study has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…These findings are consistent with the work of Sivinski et al (43) who reported a significant role for these cell populations in generating antitumor immunity against parental Panc02 tumors. The absence of synergy between IFN-α and CEA vaccine in mice with Panc02.CEA tumors was surprising considering the efficacy of the individual treatments and the synergistic effects of this combination in mice with MC38.CEA tumors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with the work of Sivinski et al (43) who reported a significant role for these cell populations in generating antitumor immunity against parental Panc02 tumors. The absence of synergy between IFN-α and CEA vaccine in mice with Panc02.CEA tumors was surprising considering the efficacy of the individual treatments and the synergistic effects of this combination in mice with MC38.CEA tumors.…”
Section: Discussionsupporting
confidence: 93%
“…Our antibody blockade experiments support a role of CD80 expression in mediating antitumor immunity. Costimulation through CD80 is likely an important mediator of adaptive immunity in the Panc02 system because CD28 -/- mice show markedly reduced survival following a challenge with the parental Panc02 cell line (43). The role of CD80 in mediating the interaction between tumor and the immune system is complex, however, because low CD80 expression is reported to contribute to tumor escape through preferential engagement of CD152 (CTLA-4) on T cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…12,16,17,[33][34][35][36] Interestingly, lymphocytes were not found to infiltrate the pancreatic tumor mass, being preferentially localized in the peripheral stroma. Furthermore, in a subset of our patients with PC, tumor infiltrating lymphocyte subsets were also evaluated.…”
Section: Discussionmentioning
confidence: 91%
“…The alteration of MUC1 in neoplasia makes it an ideal tumor antigen for use both diagnostically and in therapy, and several studies highlight the potential of the MUC1 molecule in the development of tumor-antigen-specific vaccines (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%